On the electronic properties of some metals using density-functional theory - Mustapha, Lateef Olajuwon; Oyewande, Oluwole Emmanuel; Kolebaje, Olusola Tosin (International Journal of Physical Research, 2013)
The use of density functional theory as a viable tool for investigating the electronic structure of both periodic and disordered system at ground state has been emphasized. In this study, we employ local density approximation and plane wave formalism via Quantum ESPRESSO, the selected metals was observed to exhibit degenerate but overlap bands except Copper and Silver whose inner d state function transits its broader s state. The study shows the efficacy of density functional theory as a promising tool for explaining electronic properties of metal.